A correlação entre a cultura, gestão do conhecimento e a sustentabilidade nas organizações - Tabosa, Mayra Cinara de Oliveira (2017)
The present master thesis’ goal is to evaluate the correlations between the Organization Culture, Knowledge Management – KM, and Sustainability in organizations. Therefore, the methodology applied in this study was the analysis of correlation using the Spearman’s Correlation Test in six companies of different branches, featuring a multi-case study, being also applied in one of the companies individually for a case study. The research instrument used was a questionnaire composed of 26 questions based on three themes: Edgar Schein’s cultural typology (artifacts, values and basic assumptions), Barclay and Murray’s model of Knowledge Management (mechanistic, cultural, and systematic), and the Elkington’s Triple Bottom Line (social, environmental, and economic). The results show a Correlation Matrix which distributes the relations in six scenarios, individually analyzed, both in the multi-case study, as in the case study. They were: 1. Organization Culture- Organizational Culture; 2. Knowledge Management – Knowledge Management; 3. Sustainability – Sustainability; 4. Organizational Culture – Sustainability; 5. Knowledge Management – Sustainability; 6. Organization Culture – Knowledge Management. On scenario 1 it was verified that the collaborators perception when the culture is on the first two dimensions of the model, artifacts and values. The scenario 2 called the attention to the absence of a management model knowledge-oriented. The scenario 3 stands out because of the correlation between items from the environmental and social dimensions and the difficulty of involvement with the economic dimension. The majority of weak correlations marked scenario 4, with pairs involving items from the culture model and the items of the environmental and social dimensions of sustainability. Scenario 5 also highlighted a large number of weak correlations explained by the absence of a knowledge management model within organizations that works together with sustainable measures. Lastly, the scenario 6 presented inferior correlation compared to the others, once the pairs of weak relations obtained the minimum level of the allowed range, what mean very close to the null correlations that were also highlighted, fact explained by the superficiality of the knowledge of the culture and absence of a KM model. On the other hand, by the case study it was concluded that for Scenario 1 there is a correlation between the items of the organizational culture highlighting the good perception of employees regarding the culture in which they are inserted, but not in an in-depth way. In Scenario 2, there was no correlation between the items of Knowledge Management, highlighting the absence of a knowledge-driven management, because the Environmental Management System manages the organization. In Scenario 3 it was presented correlations on sustainability, highlighting the environmental and social dimensions as strengths. Finally, Scenario 6 also found no relationship between the items, highlighting the absence of a KM model and the perception of culture focused on the visible characteristics (furniture, architecture, and equipment) and the employees’ behavior. In general, the results of the case and multi-case study showed that the correlations between Organizational Culture, Knowledge Management and Sustainability are lower in number and type than expected. Also highlighting the existence of points in each theme that, when working in organizations, may improve the results of these correlations.